Antiviral intervention strategies against RNA viruses: Roles of Paliperidone and RIG–I - Panagiotidis, Georgios Dimitrios; Justus Liebig University Giessen (My University, 2022)
Human viral respiratory pathogens influenza A virus (FLUAV) and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS–CoV–2) are a significant burden on human health. Even though antivirals are available, the infection numbers still remain significant. Recent in silico data provided insight on potential inhibitors against these viruses. One of the top hits was the schizophrenia drug Paliperidone which was predicted to disrupt the interaction of FLUAV polymerase subunit PB2 with the nucleoprotein NP and to inhibit SARS–CoV–2 protease 3CLpro. In this work the effect and mechanism of action of Paliperidone against FLUAV and effect on SARS–CoV–2 were to be determined. Paliperidone exhibited early inhibitory effect against A/PR/8/34 in RNA, protein and titer levels with the latter observed, in human airway bronchial cell system. Furthermore, Paliperidone exhibited mild inhibitory effect against other H1N1 strains in RNA, protein and viral polymerase levels, failing to affect strain A/WSN/33 PB2 627E (avian) whatsoever. In this study, was, also, in vitro proved, that Paliperidone disrupts the interaction of PB2 and NP of A/PR/8/34. Paliperidone was also found, here, to inhibit SARS–CoV–2 only on RNA levels. All these indicate that Paliperidone might represent a compound of interest for further development of FLUAV and SARS–CoV–2 antivirals. RIG–I is an innate immune cytosolic pattern recognition receptor inducing type 1 interferon response and senses RNA of FLUAV and SARS–CoV–2. RIG–I domains CARDs and helicase are indispensable for interferon response. Studies with signalling deficient RIG–I, indicated that it has direct antiviral effect against FLUAV. Thus, in this study, a set of mutations on RIG–I that affect signalling were inhibitory against A/PR/8/34 in RNA levels in kidney cells. Furthermore, in adenocarcinoma alveolar cells, the signalling deficient RIG–I DC (ΔCARD) exhibited inhibitory effect against only strain A/PR/8/34 on RNA levels, failing to affect strain A/WSN/33 PB2 627E (avian) and SARS–CoV–2. These indicate that, signalling deficient RIG–I is of interest to study for its direct antiviral activity against FLUAV.
Keywords: Virology; Immunology; Paliperidone; ddc:570